Multimodal literacy development in a higher education English Studies classroom. Issue 3 (1st October 2020) - Wünsch-Nagy, Nóra
Abstract: University students are often expected to interpret and produce multimodal texts during their studies. However, their multimodal literacy is rarely developed explicitly and students often lack the language and the knowledge to talk and write about multimodal experiences. Such expectations demand knowledge and skills to approach multimodal texts in written and spoken discourse. To explore the educational potential of artworks, museum exhibitions and other multimodal texts in language development, I designed a course for undergraduate English Studies students at a Hungarian university. The course called 'Making Meaning with Visual Narratives' was aimed at English language teacher trainees and English Studies students. Data collected during the courses comprise writing tasks, questionnaires, multimodal texts, and my teaching notes. Based on the qualitative content analysis of the data, I demonstrate the impact of image-based language development tasks on conceptual development. Both the research design and its implementation in pedagogical practice draws on social semiotic multimodal analysis, theories of literacy pedagogy and sociocultural theory.